Terahertz Polarization Splitters Based on Total and Partial Coupling in Dual Slotted Core Polymer Fiber: Comparison and Analysis - Hongzhi Chen; Guofeng Yan; Erik Forsberg; Sailing He (IEEE Photonics Journal, 2017)
Two terahertz (THz) polarization splitters based on dual slotted core polymer fiber are proposed and numerically investigated. The splitter structures are based on dual cores composed of subwavelength-scale air slots that are independently suspended within the fiber, which not only allows for single-mode propagation for the two orthogonal polarization modes with low absorption losses but enables them to couple with each other as well. Polarization splitters based on both symmetric and asymmetric dual slotted core structures, respectively, based on total and partial coupling are proposed and analyzed. The transmission modes, splitting lengths, and pertinent performance parameters of the two polarization splitters are investigated and numerically analyzed at a center-frequency of 1.0 THz. Comparisons of the two splitters with similar structural parameters are also carried out, which shows a comparably short splitting length of ∼1 cm and an ultra-low transmission loss of 0.4 dB with the asymmetric structure having a broader bandwidth and better extinction ratios.